Angle of Arrival Estimation for Terahertz-enabled Space Information Networks - Nayir, Hasan; Kurt, Gunes Karabulut; Gorcin, Ali (IEEE COMPUTER SOC, 2022)
Space information networks (SINs) empowered by Terahertz (THz) frequencies are expected to play a vital role in next-generation wireless space networks due to the unique transmission characteristics and coverage extension capabilities of SINs, owing to their high altitudes. Also, utilizing THz frequencies allows the usage of more bandwidth. However, communications in this frequency range come at the cost of extreme path loss, especially for low-orbit implementation of SINs. High gain narrow beamforming utilizing a large number of antennas can be considered to overcome substantial losses at these frequencies. Consequently, highly accurate and efficient angle of arrival (AoA) estimation algorithms are required to achieve successful beamforming and eventually to increase the signal-to-noise ratio (SNR) in SINs. To this end, we propose the utilization of a two-stage gold-MUSIC algorithm over an array of subarray (AoSA) structure for AoA estimation with lower power consumption and less hardware complexity compared to the contemporary arrays due to the reduced RF-chain in AoSA. Furthermore, we introduce an analysis of AoA estimation performance in terms of residual Doppler spread, which is a realistic metric for SINs since Doppler cannot be accurately estimated in the case of instantaneous rapid motional changes of satellites especially at high frequencies. Results show that the proposed two-staged gold-MUSIC method for AoSA provides accurate AoA estimation while being computationally efficient.
Keywords: Space information networks; angle of arrival; array of subarray; massive MIMO; residual Doppler spread; WAVE MASSIVE MIMO; CHANNEL ESTIMATION; HYBRID; TRACKING; VISION; MUSIC; Telecommunications